2013
DOI: 10.20885/ejem.vol5.iss2.art3
|View full text |Cite
|
Sign up to set email alerts
|

Infrastructure, economic growth and inequality in Indonesia land borders

Abstract: The purpose of this study is to analyze the impacts of infrastructure on economic growth and inequality in Indonesia land borders. Using static panel data regression and panel two stage least square (2SLS) estimation methods, this study shows that social infrastructure can raise per capita income. The social infrastructures being discussed are number of high schools and number of health facilities. Telecommunication facility can also raise per capita income. In addition, income inequality is found to be positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
12
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 6 publications
(9 reference statements)
4
12
0
4
Order By: Relevance
“…The district/city minimum wages coefficient value of 0.121419 means that a 1% increase in district/city minimum wages will increase income inequality by 0.121419% with the assumption of ceteris paribus. This is in line with the research by Prasetyo et al (2013) and Sungkar et al (2015) where an increase in labor income in the industrial sector (formal) will increase inequality. The increase in income in the formal sector causes the difference in labor income between the industrial sector (formal) and the agricultural sector to widen, so that this will lead to income inequality in society.…”
Section: Finding and Discussionsupporting
confidence: 92%
“…The district/city minimum wages coefficient value of 0.121419 means that a 1% increase in district/city minimum wages will increase income inequality by 0.121419% with the assumption of ceteris paribus. This is in line with the research by Prasetyo et al (2013) and Sungkar et al (2015) where an increase in labor income in the industrial sector (formal) will increase inequality. The increase in income in the formal sector causes the difference in labor income between the industrial sector (formal) and the agricultural sector to widen, so that this will lead to income inequality in society.…”
Section: Finding and Discussionsupporting
confidence: 92%
“…In these conditions, the labor force would trigger unemployment, which in turn lowers economic growth. However, these results are consistent with the results of Prasetyo et al (2013) who found that the investments do not affect the economic growth of DIY. Presumably it is because investment in YST is dominated by small industries.…”
Section: Investment I Nfluence On Economic Growthsupporting
confidence: 92%
“…Fan et al (2011) state three strategies to disperse fairly economic growth to regions namely (a) infrastructure, (b) social investment and protection and (c) government reform. Additionally, economic growth depends on investment purchase of infrastructure (Prasetyo et al, 2013). The availability and quality of infrastructure financed by government or private investment are keys of economic progress affecting the Indonesian national economic growth (Ferdinan, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Sementara itu Makmuri (2017) menemukan bahwa ketidakseimbangan jumlah infrastruktur jalan dan telekomunikasi cenderung meningkatkan ketimpangan pendapatan antarwilayah di Indonesia. Penelitian Prasetyo et al, (2013) menunjukkan bahwa infrastruktur memiliki hubungan tidak langsung dengan ketimpangan pendapatan melalui pendapatan per kapita. Fakta ini sesuai dengan hasil penelitian ini yang menjelaskan bahwa pembangunan infrastruktur provinsi di Indonesia seperti irigasi, jalan, dan air bersih berkaitan erat dengan perkembangan ekonomi yang terjadi pada provinsi tersebut.…”
Section: Gambar 3 Scatter Plot Indeks Williamsonunclassified